2020
DOI: 10.4103/ijpsym.ijpsym_439_18
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Daytime Sleepiness among the Clinicians Working in a Tertiary Care Center in Sikkim, India

Abstract: Background: Doctors in India have increased workload and are at risk for poor sleep and excessive daytime sleepiness which have not been explored much. Methods: One hundred doctors selected by convenience sampling from different departments of the hospital were assessed cross-sectionally. Physical parameters which were assessed included height, weight, blood pressure, and diabetes status. Other variables assessed included durations of duty hours and social media usage. Sleep quality and daytime sleepiness were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Prolonged sleep restriction has been reported to reduce the cognitive and clinical performance of physicians [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged sleep restriction has been reported to reduce the cognitive and clinical performance of physicians [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…These findings related to sleep in young doctors in the Indian scenario require attention, as the excessive workload compounded by the inadequate sleep in them can be a threat to the health of both the physician and the patient. Prolonged sleep restriction has been reported to reduce the cognitive and clinical performance of physicians [ 13 - 15 ]. More dangerously, the chronically sleep-deprived tend to underestimate their impairment [ 16 ], which can have serious repercussions in the scenario of patient care by a physician with cumulative sleep debt.…”
Section: Discussionmentioning
confidence: 99%
“…The studies analysed showed that the patient data was being collected from outpatient department, so the patient had a morbidity for which they had reported. Some were done on caregivers and attendants 9,10,97 of patients while they were in hospital or attending on a patient while in outpatient department. Few studies worked on general population using representative samples of college students 13,14,35,42,80,92,104 and some targeted the population in general 12,16,37,38,40,67,78,79,81,93,94 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive daytime sleepiness (EDS) remained a symptom which was found in many studies and analysis for EDS was done. Studies reporting insomnia or insomnia like features , OSA 13,22,26,27, , RLS 10,15,19,25,28,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and excessive daytime sleepiness 11,17,40,59,60,67,72,80,88,[91][92][93][94][95][96][97][98][99][100][101][102][103][104] were analysed. The details of which are tabulated in Table 1.…”
Section: Search Strategymentioning
confidence: 99%
“…14 Lack of adequate sleep also results in cardiovascular diseases and mental disorders. 15 Nightshift work can cause unrestful sleep leading to daytime somnolence, decreased alertness and an increase the risk of medical errors, occupational injuries and car accidents. 16 The general and physical fatigue, nightshift work, and increased working hours are predictors for doctors nding their patient irritating and for having less compliance in their relationship with patients.…”
Section: Introductionmentioning
confidence: 99%